Regional Matching Frictions and Aggregate Unemployment - Sanna-Mari Hynninen; Aki Kangasharju; Jaakko Pehkonen (European Regional Science Association (ERSA), 2006)
The study shows that a stochastic frontier approach applied to regional level data offers a convenient and interesting method to examine how regional differences in matching efficiency and structural factors contribute to aggregate unemployment. The study finds notable and time-wise stable differences in the matching efficiency across travel-to-work areas in Finland. If all areas were as efficient as the most efficient one, the number of hires would increase about 40 per cent. This would decrease the aggregate unemployment rate from the current 8.5 percent level to 6.0 per cent. If all the areas shared the same structural characteristics as the most favourable area, the aggregate unemployment rate would drop to 7.1 per cent.
Keywords: 330